Study on vancomycin-resistant enterococci in faecal samples from non-hospitalized individuals at MMIMSR, Haryana, India - Bera, Shyamsundar; Mehta, Sonia; Dwivedi, Manisha Bhatt; Singh, Varsha A; Paul, Rajdeep; Nongrum, Sumi (Bangladesh Journal of Medical Science, 2019)
Background: Enterococci, formerly classified with fecal streptococci, have been recognized to be of fecal origin since the beginning of this century. Method: This study was undertaken to determine the prevalence of stool colonization with vancomycin resistant Enterococcus (VRE) and also to evaluate the risk factors for colonization with vancomycin resistant Enterococcus among non- Hospitalized individuals at MMIMSR, Mullana.Test was performed for VRE isolates collected over a period of 6 months (Oct2015- March 2016). Faecal samples were collected by using sterile container from non- hospitalized individuals then to Cultures using Mac Conkey and Blood agar. After presumptive diagnosis as an enterococcus spp, 50 Enterococcal isolates were then again cultured on special VRE screen agar media to identify vancomycin resistant Enterococcus. Result: The results were further supported by modified Kirby-bauer disk diffusion method with vancomycin (30μg) as per CLSI guideline. A total of 29 (58%) Enterococcus faecalis and 21 (42%) Enterococcus faecium were detected among the faecal isolates and 2 (4%) were VRE. According to CLSI guideline isolates showing diameter of zone of inhibition ≤16mm were considered among the VRE. Chronic diseases, previous hospital stay (more than 15 days) and repeatedly antibiotic consumption was found to be significant risk factor for non-hospitalized individuals. Conclusion: There is need for programs to promote greater attention about antibiotics usage in the general population. Education of Health care workers with implementation and observation of hand-washing practices constitutes a very effective step in preventing the spread Prolonged use of vancomycin drug should not be recommended by the physician. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.334-339